COVID-19: Moral and Ethical Implications for Orthopaedic Spine Surgeons. (15th July 2021) - Min, Cris J.; Iturriaga, Cesar; Wang, Victoria; Verma, Rohit
Abstract : The rapid spread of COVID-19 has made a significant impact on healthcare systems worldwide, with a large influx of patients prompting the cancellation of elective surgery in order to conserve resources and prevent the risk of exposure to the novel virus. In this case report, we present a 66-year-old male patient, with a history of cerebral palsy and developmental disabilities, exhibiting an increasing loss of function over the course of 10 days amid the COVID-19 pandemic. The patient was initially refused transport to the hospital by emergency medical services and later transported per independent request from his surgeon. Upon admittance to the hospital, the patient was found to have severe spinal cord compression with myelopathic symptoms and underwent an anterior cervical discectomy and fusion. This case highlights the need for more specific guidelines regarding the evaluation of a spinal injury by EMS and the hospital system amid a national crisis.